Evaluation of Acute Flaccid Paralysis Surveillance System's Structure at Al-Russafa Health Directorate in Baghdad City - baktash, mohammed; Abdul Wahid, hala (Iraqi National Journal of Nursing Specialties, 2016)
Objective: evaluation of Acute Flaccid Paralysis Surveillance (AFP) System's Structure at Al-Russafa Health directorate in Baghdad City. Methodology: descriptive study using evaluation approach conducted to measure the efficiency of AFP Surveillance System structure for period from November 27th 2014 to June 30th 2015. The study adopted the non-probability multi-stage sampling approach. As nineteen health facilities under surveillance are chosen and interview is conducted with a total of 50 health worker how are involved in the AFP Surveillance System. The data are gathered from sample by using questionnaire specifically developed for each of sample stage. Results: the study results indicates that the certain of system's structure component are efficient and available such as the system owns a legal authorization and availability of field's guide that is used in AFP surveillance. On the other hand, the study proved that some of system's structure elements need to strengthen and enhance such as unavailability of special budget line, lack of necessary materials to work and lack of training for workers in the system. Recommendations: The present study recommends that there is a necessity for the distribution of AFP manual for all health institutions under surveillance as well as monitor the uses of the manual by those who are working in the system. The study also recommends the need to provide resources and material needed in the system works and the creation of a training curriculum for those who are working in fields of AFP Surveillance in order to get the maximum benefit from this system.